National expert consensus on home-administered oncologic therapies in Spain - Villegas, Eulalia; Arruñada, María; Casado, Miguel Ángel; González, Sonia; Moreno-Martínez, María Estela; Peñuelas, María Ángeles; Torres, Ana Maria; Sierra, Yanik; Seguí, Miguel Angel (Frontiers in Oncology, 2024)
The diagnosis and treatment of cancer impose a significant emotional and psychological burden on patients, families, and caregivers. Patients undergo several interventions in a hospital setting, and the increasing number of patients requiring extended care and follow-up is driving the demand for additional clinical resources to address their needs. Hospital at Home (HaH) teams have introduced home-administered oncologic therapies that represent a new model of patient-centered cancer care. This approach can be integrated with traditional models and offers benefits to both patients and healthcare professionals (HCPs). Home-administered treatment programs have been successfully piloted globally, demonstrated as a preferred option for most patients and a safe alternative that could reduce costs and hospital burden. The document aims to establish the minimum recommendations for the home administration of oncologic therapies (ODAH) based on a national expert agreement. The expert panel comprised seven leading members from diverse Spanish societies and three working areas: clinical and healthcare issues, logistical and administrative issues, and economic, social, and legal issues. The recommendations outlined in this article were obtained after a comprehensive literature review and thorough discussions. This document may serve as a basis for the future development of home-administered oncologic therapy programs in Spain.